Surveillance and control of M. chimaera infections in the Tuscany Region, Italy. (30th September 2020) - Casini, B; Tuvo, B; Totaro, M; Baggiani, A; Privitera, G
Abstract: Background: Disseminated M. chimaera infections among patients who underwent open-chest surgery with cardiopulmonary bypass have been associated with the contamination of heater-cooler devices (HCDs). The Tuscany region in the Decree 3822/2019 issued recommendations for the surveillance and control of M. chimaera infections. Methods: In three Tuscan cardiac surgery centers, the case finding was carried out through evaluation and testing of patients with a history of HCD exposure (past 6 years) was performed. Water and aerosol samples were analyzed from each HCDs to determine the microbiological parameters required by the Directive 98/83/CE and to assess the presence of non-tuberculous mycobacteria (NTMs), according to the regional protocol. Results: M. chimaera infection was not found in any patient and all clinical specimens tested negative. 22 HCDs were sampled (n.12 LivaNova, n.1 Terumo and n.9 Maquet) for a total of 114 samples (45, 8, 2 and 59 respectively). All the microbiological parameters were compliant, excepted for total microbial count at 36 °C that exceeded 100 CFU/ml in 50% (57/114) of samples and for the presence of P.aeruginosa in 10% (12/114). NTMs were detected in 16% (18/114) of HCDs: M. chimaera was identified in 11% (13/114) of samples and in 4% (5/114) M. gordonae. All aerosol samples were negative for NTMs, but in the HCDs Maquet, B.cereus were detected in 7% (4/59) of the samples, K.oxytoca in 2% (1/59), B.ursincola in 2% (1/59) and S. paucimobilis in 3% (2/59). Only S. paucimobilis was isolated also in the same HCD water sample. Conclusions: The implementation of maintenance and disinfection procedures of HCDs was able to reduce the risk of contamination and aerosolization by NTMs but not of other microorganisms. Key messages: Further strategies should be put in place for the cases finding. Moreover, reliable decontamination and identification of agents that can disrupt biofilms and increase chlorine susceptibility of mycobacteria are required.